THE IMPACT OF TAX INCENTIVE DISCLOSURE AND PROFITABILITY ON FIRM VALUE DURING THE COVID-19 PANDEMIC - Marsha Syifa Zahira Putri; Nurul Aisyah Rachmawati (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2023)
This study examines the impact of Covid-19 tax incentive of income tax article 25 disclosure and profitability during pandemic on firm value. The sampling techique used purposive sampling based on selected criterias. The population of this study are firms of tourisms, hotels and restaurants during 2020-2021 period. The study obtained sample of 50 firms. The sample data compiled from Bursa Efek Indonesia website. The analysis process used analysis stastistic descriptive, panel data regression analysis, multicollinearity testing, heteroscedasticity testing and hypothesis testing. The results showed that disclosure of Covid-19 tax incentive of income tax article 25 had no significant effect on the firm value, profitability during pandemic had positive and significant effect on company value.